Variasi Nilai Gradien Hidrolik dan Pengaruhnya terhadap Perubahan Nilai Tahanan Jenis pada Sistem Akifer Bersudut Berdasarkan Pendekatan Model Fisik - Budiono Budiono; Deny Juanda Puradimaja; Sulistijo Sulistijo (Institute for Research and Community Services (LPPM) ITB, 2003)
The core of this research is simulation on a physical model of inclined confined aquifer in laboratory scale. The model dimensions is 79.50 cm long, 78.00 cm wide, and 10.00 cm tall. The aquifer is simulated as single confined aquifer with thickness of 8 cm. The aquifer material is composed of coarse sand with good gradation and has uniformity coefficient of 7.105. The measurements consist of elevation head (z), pressure head (hp), total head (h), and resistivity with Schlumberger configuration. The confined aquifer layer is set up to be horizontal. Then, in order to get the hydraulic gradient and dip layer variations, the position of the model box is inclined with varied degree of: 00, 100, 200, and 270. To get the most representative result, the resistivity is measured with line spread parallel to strike and perpendicular to strike.The analysis shows that the increase of the hydraulic gradient (i) have the tendency to cause the decrease of true resistivity values (Ï). Based on the line spread direction and R2 values, there are 2 representatives equations as follows: 1). With line spread parallel to strike:4,88ln()64,60Ï=âˆ’+i;R2=0,95. 2). With line spread perpendicular to strike without correction on AB/2 and K value:Ï=;R3,80ln()58,20âˆ’+i2=0,99.